Hubungan Penjaminan Mutu Terhadap Kepuasan Pelanggan dan Reputasi Perusahaan Ekspedisi PT XYZ - Libbya Safha Salsabila; Mumu Komaro; Saskia Kanisaa Puspanikan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Competition in the shipping industry encourages companies to improve service quality through quality assurance systems to enhance customer satisfaction and corporate reputation. This study aims to identify the relationship between quality assurance, customer satisfaction, and corporate reputation at PT XYZ. A quantitative approach with a causal design was adopted. Data collection was conducted through a questionnaire survey of active customers selected using a proportionate stratified random sampling method. The data were obtained from descriptive statistics, correlations, and multiple linear regressions. This study is expected to produce findings that quality assurance contributes positively to customer satisfaction and corporate reputation, while also providing a basis for improving service quality.